Correlation of CXCL3 levels, Inflammatory Markers, and COVID-19 Infection with Severity of Asthma in Asthmatic Patients - Obaid, Rana Fadhil; Abbas, Ebtihal Chiad; Alyasiri, Israa Ketab (Medical Science Journal for Advance Research, 2025)
Background: Asthma is a chronic inflammatory disorder of the airways influenced by a complex network of cytokines and chemokines, among which CXC chemokine ligand 3 (CXCL3) plays an important role and has been linked to airway remodeling and disease severity. Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, induces systemic immune dysregulation with elevated inflammatory biomarkers such as C-reactive protein (CRP), ferritin, and D-dimer. The interaction between CXCL3-mediated airway inflammation and systemic inflammatory responses in asthmatic patients during COVID-19 infection remains insufficiently elucidated, with limited data clarifying its contribution to disease severity and outcomes. Objective: To evaluate the correlation of serum CXCL3 and classical inflammatory markers (CRP, ferritin, D-dimer) with asthma severity among patients with and without COVID-19 infection and to determine their relationship with lung function (FEV₁) and predictors of severe asthma. Methods: A cross-sectional study was conducted on 200 asthmatic patients, stratified according to COVID-19 infection status (76 positive, 124 negative). Demographic, clinical, and laboratory parameters were analyzed. Serum levels of CXCL3 and inflammatory markers (CRP, ferritin, and D-dimer) were compared between groups and correlated with asthma severity and FEV₁. Results: COVID-19-positive asthmatics exhibited significantly higher levels of CXCL3 (241.5 ± 83.7 vs. 173.8 ± 76.4 ng/mL, p<0.001) and inflammatory markers, along with lower FEV₁ (54.3 ± 17.2 vs. 62.1 ± 18.9; p=0.003) compared to COVID-19-negative patients. CXCL3, CRP, and D-dimer levels increased progressively with asthma severity (p<0.001), furthermore, significant positive correlations were observed between CXCL3 and asthma severity (r = 0.62) as well as between CXCL3 and CRP (r = 0.41). Logistic regression revealed FEV₁ <60% as an independent predictor of severe asthma (OR 3.12, 95% CI 1.78–5.47, p<0.001), whereas COVID-19 infection showed an inverse association with severe asthma (OR 0.48, 95% CI 0.25–0.91, p=0.026). Conclusion: Serum CXCL3 and systemic inflammatory markers are significantly associated with asthma severity and lung function impairment, particularly in the presence of COVID-19 infection. CXCL3 may serve as a potential biomarker for assessing asthma severity and guiding clinical management in patients with concurrent COVID-19.